Recensions / Book Reviews - Arnopoulos, Paris (Études helléniques / Hellenic Studies, 1997)
Ann Cacoullos: "Women in the Political Culture of Greece" Athens University Press, 1996. 215 pp. Thanos Veremis: "The Military in Greek Politics: From Independence to Democracy" Black Rose Books, Montreal, 1997. 225 pp. G. T. Allison & K. Nicolaidis (Eds): "The Greek Paradox: Promise vs Performance" MIT Press, Cambridge, 1997.180 pp.